Concomitant Pathogenic Mutations and Fusions of Driver Oncogenes in Tumors - Zhang, Runjiao; Dong, Li; Yu, Jinpu (Frontiers in Oncology, 2021)
Driver oncogene alterations have always been one of leading causes in the process of occurrence and development of tumors. And the effects of driver oncogene alterations on tumorigenesis and progression in different kinds of tumors have been studied heatedly. And the roles that the driver oncogenes alterations play have been elucidated clearly in previous studies. The phenomenon of concomitant driver oncogenes mutations and driver genes fusions has gained much concentration in the past two decades. And a growing number of studies reported this phenomenon, either coexistence or mutually exclusivity. Here we reviewed on the phenomenon of concomitant mutations in three common types of carcinomas—lung cancer, thyroid cancer, and leukemia, which have been studied relatively more detailed and more general compared with others.